A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae) - Benjamin, Suresh P. (Zootaxa, 2017)
The crab spider genus Angaeus Thorell, 1881 currently contains 10 described species (Benjamin 2013; WSC 2017). All species of the genus are restricted to tropical Asia. The aim of this correspondence is to illustrate and describe a new species of the genus characterized by a number of features previously found in the genera Angaeus, Borboropactus Simon, 1884, Epidius Thorell, 1877 and Geraesta Simon, 1889. The most unusual feature is the elongated tibia of the male palp that was previously thought to be diagnostic of Epidius (Figs 1, 2, 8; character 1 in Benjamin 2011; Benjamin 2017). However, the new species lacks tibial macrosetae (Figs 1, 2, 8) and lacks a flexibly attached MA, both also being characteristics of Epidius (characters 2 and 18 in Benjamin 2011). Furthermore, this new species differs considerably in general appearance from all known species of Epidius.